The medieval roots of antisemitism continuities and discontinuities from the Middle Ages to the present day - Adams, Jonathan 1971 December 19-; Hess, Cordelia (Routledge, 2018)
This book presents a fresh approach to the question of the historical continuities and discontinuities of Jew-hatred, juxtaposing chapters dealing with the same phenomenon - one in the pre-modern, one in the modern period. How do the circumstances of interreligious violence differ in pre-Reformation Europe, the modern Muslim world, and the modern Western world? In addition to the diachronic comparison, most chapters deal with the significance of religion for the formation of anti-Jewish stereotypes. The direct dialogue of small-scale studies bridging the chronological gap brings out important nuances: anti-Zionist texts appropriating medieval ritual murder accusations; modern-day pogroms triggered by contemporary events but fuelled by medieval prejudices; and contemporary stickers drawing upon long-inherited knowledge about what a "Jew" looks like. These interconnections, however, differ from the often-assumed straightforward continuities between medieval and modern anti-Jewish hatred. The book brings together many of the most distinguished scholars of this field, creating a unique dialogue between historical periods and academic disciplines.--
Keywords: Antisemitism / History